Pharmacology and Applications of Naturally Occurring Iridoids - Dinda, Biswanath (Springer International Publishing : Imprint: Springer, 2019)
In this book, the author provides expert analysis on naturally occurring iridoids, their chemistry and their distribution in plants and insects. Particular attention is given to the pharmacology of iridoids and their prospective applications in pharmaceutical and agricultural industries. Iridoids are found in a wide variety of plants and some insects, and they are structurally derived from monoterpenoid natural products. In the first two chapters of this book, the author describes the iridoids classification, occurrence and distribution in plants and insects. The following chapters cover different chromatographic and spectroscopic techniques that can be used to identify and quantify iridoids in herbal formulations, and also the biosynthesis of iridoids, in which the reader will discover a metabolomics and transcriptomics analysis to identify the genes involved in the biosynthesis. The final chapters provide insights on several pharmacological activities of iridoids, their physiological role in insects, pharmacokinetics in mammals, insects and microorganisms, and their applications in medicine and agriculture. This book will engage students and researchers interested in the chemistry of natural products, and it will also appeal to medicinal chemists and practitioners working in the design of new herbal drugs with bioactive pure iridoids.